أثر الازمة الاقتصادية في الامن الغذائي لبلدان نامية مختارة للمدة 1980-2009 - امنة عبدالاله الحسون (PROSPECTIVE RESEARCHES, 2023)
Economies of developing countries during their development face crises from time to time. These crises vary in severity and circumstances. They began to be a food crisis and thus a global economic crisis because of the unprecedented global economic recession which is expected to continue. Mechanisms and solutions differ according to the differences in interpreting the crises on the one hand, and analyzing its range on the other hand. It is clear that economic crises according to this research has a large effect in retreating of food security in the countries under the study because these countries depend on one source in their economy and on its exports of raw materials. These countries are considered to be the least developing ones. The analysis a high relative has shown importance of the index ratio debt service to total production local in each of the following countries sade as (Bangladesh, Chana, Nicaragua, Zambia and Armenia) with a negative significant impact for each of them. So we have to take care to set out structural agriculture policy to the external debt and its service and rescheduling to ensure that countries may not to face any debt crises by which it can affect its infrastructure and work on achieving an economic balance in total polices between economics of supply and demand.